Effectiveness of the Communities Care programme on change in social norms associated with gender-based violence (GBV) with residents in intervention compared with control districts in Mogadishu, Somalia. Issue 3 (13th March 2019) - Glass, Nancy; Perrin, Nancy; Marsh, Mendy; Clough, Amber; Desgroppes, Amelie; Kaburu, Francesco; Ross, Brendan; Read-Hamilton, Sophie
Abstract : Objective: Determine the effectiveness of the Communities Care programme (CCP) on change in harmful social norms associated with gender-based violence (GBV) and confidence in provision of services with residents in intervention compared with control district. We hypothesised that residents in the intervention district would report a decrease in support for harmful social norms and increase in confidence in services in comparison with control district. Setting: The study was conducted in Mogadishu, Somalia. Participants: In the intervention district, 192 community members (50% women) completed baseline surveys with 163 (84.9%) retained at endline. In the control district, 195 community members (50% women) completed baseline surveys with 167 (85.6%) retained at endline. Intervention: CCP uses facilitated dialogues with community members to catalyse GBV prevention actions and provides training to diverse sectors to strengthen response services for GBV survivors. Results: Residents in the intervention district had significantly greater improvement in change in social norms: (1) response to sexual violence (b=−0.214, p=0.041); (2) protecting family honour (b=−0.558, p<0.001); and (3) husband's right to use violence (b=−0.309, p=0.003) compared with control district participants. The greatest change was seen in the norm of 'protecting family honour' with a Cohen's d effect size (ES) of 0.70, followed by the norm 'husband's right to use violence' (ES=0.38), and then the norm of 'response to sexual violence' (ES=0.28). Residents in intervention district had a significantly greater increase in confidence in provision of GBV services across diverse sectors than the control district (b=0.318, p<0.001) with an associated effect size of 0.67. There were no significant differences between residents in intervention and control districts on change in personal beliefs on the norms. Conclusion: The evaluation showed the promise of CCP in changing harmful social norms associated with GBV and increasing confidence in provision of services in a complex humanitarian setting.